Maturation block in childhood cancer - Behjati, Sam; Gilbertson, Richard J.; Pfister, Stefan (Cancer discovery, 2021)
Summary: The key differences between tumors arising in children and those in adults stem from the cellular origin of cancer at different ages, with adult cancers arising within aging cell hierarchies, as a consequence of accumulated damage and mutagenesis, in contrast to childhood tumors that are born in aberrantly developing tissues. A distinct biological property of childhood tumor cells—a block of developmental maturation—may hold the key to advancing the treatment of childhood cancer beyond cytotoxic strategies.
Gesehen am 03.08.2021